A pilot feasibility study exploring the practising of compassionate imagery exercises in a nonclinical population. (10th October 2015) - McEwan, Kirsten; Gilbert, Paul
Abstract : This study assessed the acceptability of practising compassionate imagery as an online task without clinician support. Participants completed questionnaires at baseline, after, and 6 months of follow‐up. Participants engaged safely and successfully with the tasks. There were significant improvements in questionnaire scores which were largely maintained over 6 months. Practitioner points: People can practise compassionate imagery tasks in an unsupervised way from online recordings and not suffer adverse effects (even with higher baseline scores in self‐criticism). Compassionate imagery recordings may be used as an adjunct to improve traditional psychotherapy.